The Legitimacy of CSR Actions of Publicly Traded Companies Versus Family-Owned Companies - Panwar, Rajat (Journal of business ethics, 2014)
Corporate social responsibility (CSR) is one of the ways through which companies gain legitimacy. However, CSR actions themselves are subject to public skepticism because of increased public awareness of greenwashing and scandalous corporate behavior. Legitimacy of CSR actions is indeed influenced by the actions of the company but also is rooted in the basic cultural values of a society and in the ideologies of evaluators. This study examines the legitimacy of CSR actions of publicly traded forest products companies as compared to family-owned forest products companies. Results indicate a lower legitimacy for CSR actions of publicly traded companies than for family-owned companies. The study also examines the effect of social responsibility orientation (SRO) of evaluators on the legitimacy accorded to companies' CSR actions. We found that SRO was negatively associated with legitimacy, especially for women. Perceived profitability of companies was negatively associated with legitimacy of CSR actions for publicly traded but not for family-owned companies.